2019
DOI: 10.13031/aea.13142
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Thermal Properties of Chia, Kañiwa, Triticale, and Farro Seeds as a Function of Moisture Content

Abstract: Abstract.The knowledge of physical and thermal properties in cereals, grains, and oilseeds establishes an essential engineering tool for the design of equipment, storage structures, and processes. The physical properties and thermal properties for Chia, Kañiwa, Farro, and Triticale grains were investigated at three levels of moisture content: 10%, 15%, and 20% (d.b.). Physical properties included 1000-seed weight, dimensions, mean diameters, surface area, volume, sphericity, and aspect ratio. Results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
3
5
1
1
Order By: Relevance
“…Meanwhile the imported seeds had a black or deep dark yellow color similar to that of dark coffee. Suleiman et al (2015) showed that the lightness degree (L*), redness (a*) and yellowness (b*) of chia seed color differed from 41.3 to 42, 3.19 to 3.61 and 7.43 to 8.61, respectively. The levels of these color attributes increased with rise of seed moisture from 10 to 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile the imported seeds had a black or deep dark yellow color similar to that of dark coffee. Suleiman et al (2015) showed that the lightness degree (L*), redness (a*) and yellowness (b*) of chia seed color differed from 41.3 to 42, 3.19 to 3.61 and 7.43 to 8.61, respectively. The levels of these color attributes increased with rise of seed moisture from 10 to 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in W1000, observed and the same trend was reported for chia seeds, kaniwa, farro and triticale by Suleiman et. al., (2015).…”
Section: One Thousand Seed Weightsupporting
confidence: 86%
“…The average maximum seed length and width were 1.20 ± 0.22mm and 1.10 ± 0.20 respectively. These values are less than the range of values obtained from chia seeds but slightly higher than the values obtained for kaňiwa (Suleiman et. al., 2015).…”
Section: Seed Dimensionscontrasting
confidence: 73%
See 2 more Smart Citations